Produktion : Made in Germany Drei - Mattheis, Lisa Felicitas (Köln : Snoeck Verlagsgesellschaft mbH, 2017)
Alexi-Meskhishvili, Ketuta ; Balema, Olga ; von Bismarck, Julius ; Blightman, Juliette ; Bock, Katinka ; BPA. Berlin Program for Artists (Bierwirth, Maria Anna ; Duchovny, Sofia ; Frater, Richard ; Goyette, Mia ; Hegner, Sylvester ; Klinger, Johanna ; Koetting, Nile ; Revoir, Grayson ; Yammad, Miriam) ; Brandes, Carina ; Das Numen (Charrière, Julian ; Greiner, Andreas ; Hoffmann, Markus ; Kiessling, Felix) ; Fehr, Henning ; Rühr, Philipp ; Fudakowski, Kasia ; Hahn, Sascha ; Henke, Lena ; Henkel, Calla ; Pitegoff, Max ; IMPURE FICTION ; Knorr, Daniel ; Kretschmann, Schirin ; Kurz, Veit Laurent ; Laric, Oliver ; Lien, Amy ; Camacho, Enzo ; Lindner, Lotte ; Steinbrenner, Till ; lonelyfingers ; Empire, Peles ; de Rooij, Willem ; Ruff, Thomas ; Sapountzis, Yorgos ; Si-Qin, Timur ; Steyerl, Hito ; Studio for Propositional Cinema ; Vogel, Raphaela
The third edition of Made in Germany, which is again being mounted by the Kestner Gesellschaft, the Kunstverein Hannover, and the Sprengel Museum Hannover, opens on June 2, 2017. Ten years after the first edition, the cross-institutional exhibition project for the first time has a thematic focus: the concept of production. While contemporary art production may be characterized by global networking and mobility, it still requires an infrastructure, meaning art schools, exhibition venues, and production sites alike, which make up Germany’s art and cultural landscape. A more intense self-inquiry into artistic approaches has become noticeable in recent years—including with respect to the specific conditions of art production in Germany. Artists address producing art in particular in collective work, processual methods, and in time-based formats as well as in the examination of production processes and presentation venues. The selection of the 41 artistic positions in the exhibition, for which new site-specific works have been specifically created, represents these current trends. (provided by publisher)
Produktion. Made in Germany, Kestner Gesellschaft - Kunstverein Hannover - Sprengel Museum Hannover, Hannover, June 3 - September 3, 2017
boek